Differences in kinematic parameters between elite sprint swimmers - Durovic, M.; Nikolic, M.; Madic, D.; Okicic, T. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The purpose of this research was to determine the differences in kinematic parameters between elite swimmers compared to the achieved results in the 50 m freestyle (t50). Methods: Forty elite male sprint swimmers (participants of the preliminaries, semi-finals and finals events at the open championship of Serbia 2017 in 50 m free) were recorded (GoPro Hero 4 black edition. 120 fps) and analyzed with specialized software (Kinovea 0.8.15). The sample variables consisted of seven kinematic parameters: start time up to 10 meters (t10m in s), stroke length in the first 25 m (SL1_50 in m). stroke length in second 25 m (SL2_50 in m). stroke index in the first 25 m (SI1_50), stroke index in second 25 m (SI2_50), stroke rate in the first 25 m (SR1_50 in stroke/min) and stroke rate in the second 25 m (SR2_50 in stroke/min). The camera was set at a sagittal level in relation to the length of the pool at 25 m. while the calibration and marking of the distance was carried out using the lane buoys. The swimmers were divided by cluster analysis (K-Means Cluster Analysis), in three groups compared to the results achieved at the mentioned events. The first group consisted of fastest swimmers, i.e. swimmers whose results of 50 m free are above the average in relation to the total sample of swimmers (G1_50; t50 = 23.53 ± 0.27 s. n = 6:). The second group consisted of swimmers with average results (G2_50; t50 = 24.54 ± 0.33 s, n = 18;) and the third group consisted of swimmers with achieved results below average (G3_50;t50 = 25.52 ± 0. 33 s. n =16). In order to determine statistically significant differences between groups in kinematic parameters in relation to the achieved results, a univariate variance analysis (ANOVA. Tukey HSD) was applied. Results: The results show that there is a statistically significant difference in the kinematic parameters between elite swimmers represented by: t10_50 (F = 16.79, p = 0.000; G1_50-G2_50 = -0.19s. p = 0.016; G1_50-G3_50 = -0.37s. p = 0.000; G2_50-G3_50 = -0.18s. p = 0.002). SL2_50 (F = 4.44, p = 0.019: G1_50-G2_50 = 0.008. p = 0.048: G1_50-G3_50 = 0.10. p = 0.015: G2_50-G3_50=0.02. p=0.747) and SI2_50 (F = 13.49. p = 0.000: G1_50-G2_50 = 0.25. p = 0.001. G1_50-G3_50 = 0.34. p = 0.000; G2_50-G3-50=0.03. p=0.124). Conclusion: It can be concluded that swimmers who have the ability to be fast at the start and to maintain the effectiveness of stroke length and stroke index in the second part of the race have predispositions to achieve better results in sprint disciplines, which suggests that kinematics parameters and starting abilities should be monitored and improved in the training process so that the results at the competitions will be better.